HPV-Related Multiphenotypic Sinonasal Carcinoma Presenting as a Gingivobuccal Sulcus Lesion - Kalita, Abhijit; Harlalka, Munmun (Annals of Pathology and Laboratory Medicine, 2025)
Introduction: HPV-related multiphenotypic sinonasal carcinoma (HMSC), originally known as HPV-related carcinoma with adenoid cystic carcinoma-like features, is a distinct neoplasm that is seen in the sinonasal tract which exhibits features of both surface-derived neoplasm and salivary gland carcinoma (particularly adenoid cystic carcinoma), and is associated with high-risk human papillomavirus (HPV). Case Presentation: A 52-year-old man was evaluated for an ulcer over the left upper alveolus and retromolar triangle. It was diagnosed initially as conventional squamous cell carcinoma and treated accordingly for over 2 years. Over time, there was an increase in the size of the lesion up to 5x4x4cms, epicentered in the left maxilla. However, there was no evidence of lymph node involvement or distant metastasis. Re-biopsy of the lesion in the left gingivo-buccal sulcus was done and evaluated. The histomorphology showed an overlap between a surface-derived neoplasm (squamous cell carcinoma) and a salivary gland neoplasm (adenoid cystic carcinoma). Ancillary methods also detected multiphenotypic differentiation (p16 block positivity along with ductal epithelial component expressing PAN-CK, CK7, CD117, and myoepithelial component expressing S-100, p63 and SMA) which lead to the identification of the lesion as HMSC. Conclusion: As the HMSC entity is distinct from conventional squamous cell carcinoma and salivary gland carcinoma, it is important to identify its histological characteristics and differentiate it from its mimickers.